Generation Y consumers’ buying behaviour in fashion apparel industry: a moderation analysis - Valaei, Naser *; Nikhashemi, Seyedrajab * (Emerald, 2017)
Purpose The advent of media and technology has led to growing inclination among Generation Y (Gen-Y) consumers towards diverse fashion influences and they tend to dress either to fit in with their peers or to articulate self-identity and conform to the society. This trend has become a fashion dilemma and the purpose of this paper is to leverage on this matter by investigating the factors influencing the Gen-Y consumers’ attitude and purchase intention towards fashion apparel.